2019
DOI: 10.1136/bcr-2018-229045
|View full text |Cite
|
Sign up to set email alerts
|

Lethal multiple pterygium syndrome

Abstract: Multiple pterygium syndrome of lethal type is a very rare genetic condition affecting the skin, muscles and skeleton. It is characterised by minor facial abnormalities, prenatal growth deficiency, spine defects, joint contractures, and webbing (pterygia) of the neck, elbows, back of the knees, armpits and fingers. We present a case of lethal multiple pterygium syndrome born at our hospital proven by the genetic analysis showing a double homozygous mutation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…The differential diagnosis includes Bartsocas–Papas, FADS ( fetal akinesia deformation sequence , also known as Pena–Shokeir syndrome type I), Neu–Laxova, and arthrogryposis multiplex; Congenital restrictive myopathy and Bruck syndrome. And the diagnosis is confirmed with genetic examinations 5,13 …”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The differential diagnosis includes Bartsocas–Papas, FADS ( fetal akinesia deformation sequence , also known as Pena–Shokeir syndrome type I), Neu–Laxova, and arthrogryposis multiplex; Congenital restrictive myopathy and Bruck syndrome. And the diagnosis is confirmed with genetic examinations 5,13 …”
Section: Discussionmentioning
confidence: 93%
“…And the diagnosis is confirmed with genetic examinations. 5,13 The early diagnosis of MPS is difficult because the only sonographic features present in the first trimester are increased nuchal translucency and fetal hydrops. But we did not find this presentation in second trimester sonography.…”
Section: Discussionmentioning
confidence: 99%
“…CHRNA1 (MIM 100690), CHRND (MIM 100720), CHRNG (MIM 100730), RAPSN (MIM 601592), DOK7 (MIM 610285), CNTN1 (MIM 600016), and SYNE1 (MIM 608441) gene mutations would lead to fetal akinesia deformation sequence and/or multiple pterygium syndrome (MPS) (Chen, 2012), a rare autosomal recessive inherited disorder mainly manifested as arthrogryposis multiplex congenita, pterygia of the neck, fingers, and antecubital, popliteal, and intercrural areas, developmental delay, and facial, vertebral, and genital anomalies (Penchaszadeh and Salszberg, 1981;Ramer et al, 1988). The prevalence of MPS remains uncertain and is supposed to be less than 1/100,000, as reported by a previous study (Mohtisham et al, 2019). MPS is typically divided into prenatally lethal and nonlethal types (Barros et al, 2012;Chen, 2012).…”
Section: Introductionmentioning
confidence: 98%
“…The nonlethal form of MPS is also known as Escobar syndrome. The lethal multiple pterygium syndrome (LMPS) is a rare autosomal recessive inherited disorder characterized by intrauterine growth retardation, multiple pterygia, and flexion contractures, causing severe arthrogryposis and fetal akinesia (Vogt et al, 2008;Joshi et al, 2016;Mohtisham et al, 2019). In addition, although the most common inheritance model is autosomal recessive, the autosomal dominant and X-linked inheritance has also been reported (Tolmie et al, 1987;Meyer-Cohen et al, 1999;Chong et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the CHRND (MIM 100720) gene, which can cause four main types of congenital myasthenic syndrome (CMS): LMPS (MIM 253290), slow-channel CMS (MIM 616321), fast-channel CMS (MIM 616322), and AChR deficiency CMS (MIM 616323), is encoded by the δ subunit ( Mishina et al, 1986 ; Engel et al, 2015 ). At the same time, to date, the genes RAPSN (MIM 601592), nebulin ( NEB ; MIM 161650), CHRNA1 (MIM 100690), and CHRNG (MIM 100730) also cause varying pathogeneses in LMPS, with CHRNG mutations been observed in 30% of the cases ( Morgan et al, 2006 ; Abdalla et al, 2017 ; Mohtisham et al, 2019 ). In adddition, previous studies have reported that LMPS can also be caused by uniparental disomy (UPD) of chromosome two carrying the pathogenic variant of CHRND (NM_000751.2) ( Shen et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%